The Role of Caregivers in Elder Care during Coronavirus Disease-2019 Outbreaks (KEMAS: Jurnal Kesehatan Masyarakat, 2021)
The elderly and their caregivers are at higher risk from Coronavirus Disease-2019, particularly for elderly with chronic health conditions. To prevent the transmission of the virus, those elderly issued strict physical distance, restricting most interactions between the elderly and their caregivers. On the other side, caregivers can serve as crucial and trusted partners in the elderly’s care to curb the spread of the COVID-19 virus. Hence, this study aims to analyze the knowledge, attitudes, practices (KAP), and the role of caregivers in providing services to the elderly during the outbreaks. A descriptive quantitative study was conducted from May to June 2020. The survey was utilizing Google Forms in four cities in Indonesia. A total of 317 out of 400 participants had completed the survey. The knowledge of the COVID-19 score was 79.50%, attitude 92.11%, and practice 90.54%. The caregivers’ role in protecting the elderly from COVID’s infection was about 98.42%. They could continue their routine activities during physical distancing 84.54%, treated elderly by not going to the hospital (60.04%), not visited any crowded place, wore masks and washed their hand after activity (87.38%). They agreed that government would finally successfully control COVID-19 (90.22%). This study concluded that the knowledge, attitude, practice and role of caregivers on COVID-19 effectively prevents the caregivers neglecting the elderly during the COVID-19 outbreak. Future information on elderly care need to consider not just the risks of the virus, but also the healthy lifestyle.